Efecto de la temperatura y tiempo de hidrólisis con NaOH en la obtención de péptidos solubles de harina de semillas residuales de tarwi (Lupinus mutabilis) variedad criolla. - Ávila Yupanqui , Leydi Rene (2020)
Abstract The present investigation had as objective to evaluate the effect of the temperature and time of hydrolysis with NaOH in obtaining soluble peptides from the flour of seeds of Lupinus mutabilis, creole variety. The flour was previously deluphuptized, defatted and partially hydrolyzed with α-amylase (57º C, 208 min, pH: 5.5 and 0.01 g enzyme / kg substrate). The response surface method was used and a Rotable Central Compound Design (DCCR) was used, for two factors: Temperature and time. The initial characterization of the tarless meal showed a high content of protein (43.53 ± 0.04 g /100 g), lipids (25.41 ± 0.03 g /100 g) and ash (1.40 ± 0.07 g/100 g). The alkaline hydrolysis with NaOH was performed at pH 10, 1/25 flour: solvent ratio, time between 10 to 90 minutes and temperature between 25 ° C - 50 ° C. The quantification of the peptides was carried out by the Lowry method. The results obtained indicated that the highest concentration of soluble peptides was 7,204 mg / ml, which presented treatment at 46.3°C for 78 minutes. The mathematical model that allows predicting the concentration of soluble peptides is: Y = -7.8711 + 0.5574*X1 - 0.0084*X12 - 0.0008*X22 + 0.0032*X1*X2.; where Y is the concentration of soluble peptides in mg / mL, X1 the temperature (° C) and X2: time (minutes). Statistical analysis showed that there is a high significance value of the independent variables (time and temperature) with respect to the response variable (soluble peptides) (p <0.05).